1997
DOI: 10.1071/zo96066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wavelength of Light and Pulse Magnetisation on Different Magnetoreception Systems in a Migratory Bird

Abstract: Two hypotheses on magnetoreception in animals are currently discussed. The first hypothesis is based on light-dependent processes associated with the visual system, while the second hypothesis suggests that magnetoreception is based on biogenic magnetite. Both mechanisms are supported by experimental evidence, but whether the information they provide involves the magnetic compass or the ‘map’ is still open. In order to identify the relevance of light-dependent or magnetite-transduced processes in magnetorecept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 40 publications
4
55
0
1
Order By: Relevance
“…A navigation system presumed to be based on experience has also been shown in caged adult migrants (27,28). However, previous experiments that tested migratory orientation in cages suggested that juveniles are able to compensate for the displacement.…”
Section: Discussionmentioning
confidence: 96%
“…A navigation system presumed to be based on experience has also been shown in caged adult migrants (27,28). However, previous experiments that tested migratory orientation in cages suggested that juveniles are able to compensate for the displacement.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, an effect of the pulse was not observed in young, inexperienced migrants (Munro et al 1997) and it was suppressed in birds, whose ophthalmic nerve had been anaesthetized (Beason & Semm 1996). In both the cases, the birds continued in their normal Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Details of these results allowed an interpretation of these findings: the pulse effect was restricted to old, experienced birds, thus indicating that a learned system was involved, whereas the disorientation under long-wavelength light was observed in old, experienced and young, inexperienced migrants alike, thus suggesting an effect on an innate system (Munro et al 1997). Hence, we tentatively concluded that the magnetite-based mechanism provided birds with magnetic information that was interpreted with the help of the experience-based navigational 'map' to indicate position, while radical pair processes provided directional information for the innate magnetic compass (Munro et al 1997;see Wiltschko & Wiltschko 2005;Wiltschko & Wiltschko 2006 for review).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations